Nucleic Acid-Based Treatments Against COVID-19: Potential Efficacy of Aptamers and siRNAs - Khanali, Javad; Azangou-Khyavy, Mohammadreza; Asaadi, Yasaman; Jamalkhah, Monire; Kiani, Jafar (Frontiers in Microbiology, 2021)
Despite significant efforts, there are currently no approved treatments for COVID-19. However, biotechnological approaches appear to be promising in the treatment of the disease. Accordingly, nucleic acid-based treatments including aptamers and siRNAs are candidates that might be effective in COVID-19 treatment. Aptamers can hamper entry and replication stages of the SARS-CoV-2 infection, while siRNAs can cleave the viral genomic and subgenomic RNAs to inhibit the viral life cycle and reduce viral loads. As a conjugated molecule, aptamer-siRNA chimeras have proven to be dual-functioning antiviral therapy, acting both as virus-neutralizers and replication-interfering agents as well as being a siRNA targeted delivery approach. Previous successful applications of these compounds against various stages of the pathogenesis of diseases and viral infections, besides their advantages over other alternatives, might provide sufficient rationale for the application of these nucleic acid-based drugs against the SARS-CoV-2. However, none of them are devoid of limitations. Here, literature was reviewed to assess the plausibility of using aptamers, siRNAs, and aptamer-siRNA chimeras against the SARS-CoV-2 based on their previously established effectiveness; and discussing challenges lie in applying these molecules.